APLIKASI PROBIOTIK WARETHA PADA PETERNAK ITIK PETELUR DI NAGARI ATAR KECAMATAN PADANG GANTING KEBUPATEN TANAH DATAR - Wizna Wizna; Rusfidra Rusfidra; M. I. Rias; R. Andika (Jurnal Hilirisasi IPTEKS, 2022)
This program was conducted on the Nagari Atar duck farm, Padang Ganting District, Tanah Datar Regency, West Sumatra Province. This activity aims to overcome the problems of developing ducks such as the high price of feed, the lack of information about the preparation of rations based on local ingredients and the traditional maintenance system. In addition, this activity aims to increase the knowledge of farmers about probiotics and their benefits and how to use them, so that the use of Waretha probiotics in laying ducks can overcome problems in the development of laying ducks business, such as reducing the high cost of feed and making it more affordable for smallholder farms. The method of activities carried out to overcome this problem can be done with several approaches, namely learning in the form of training and mentoring with a team of service as facilitators in the form of introducing WARETHA probiotic products and practicing how to use them and how to prepare rations for laying ducks at various age levels, so that the use of Waretha probiotics can suppress high feed costs. The results of this activity are reducing production costs, increasing farmers' income and being able to reduce the smell of feces around the cage which is environmentally friendly as well as increasing the knowledge of farmers about the benefits and how to use Waretha probiotics. The conclusion of this community service activity is that it can increase the knowledge of farmers about the management of laying ducks by using Waretha probiotics and the use of local feed ingredients, so as to reduce production costs and reduce feed costs.